Tobacco Taxation in the European Union : An Overview - Bouw, Annerie (World Bank, Washington, DC, 2017)
The European Union has a long experience in tobacco tax harmonization, which provides useful lessons learned. In the European Union, tobacco tax harmonization took place in stages, and currently all Member States have agreed upon definitions, tax base, and minimum excise duty rates for all product categories of manufactured tobacco. Tobacco tax harmonization pursues several different objectives, among which some might appear contradictory at first sight. This is the case in the European Union, where ensuring collection of revenues and ensuring a high level of health protection are, among others, objectives of tobacco tax harmonization. Reaching the objective to ensure a high level of health protection implies a declining consumption and thus declining revenues. It therefore seems impossible to reach both objectives with the same legal provisions. However, experience in the European Union proves otherwise. Lower tobacco consumption and the decrease in revenue this would otherwise generate have been compensated by increased rates, thereby reaching both objectives.